Зародження і розвиток ідей українського конституціоналізму (XVIII – 30-ті р. ХХ ст.) - Ковальчук, В.; Білостоцький, С.; Kovalchuk, V.; Bilostotsky, S. (СНУ ім. Лесі Українки, 2018)
Стаття присвячена дослідженню конституційних ідей, концепцій та доктрин розвитку українського суспільства, що сформувалися і розвивалися у XVIII - 30-х р. ХХ ст. Встановлено, що конституційні концепції суспільного устрою українців творилися під впливом наукового аналізу історичного досвіду українців, політичних умов в яких вони перебували, європейських теорій розуміння сутності та вдосконалення людського соціуму, а саме: ідей слов'янофільства, теорій лібералізму, соціалізму, націоналізму. The article is devoted to the study of the constitutional ideas, concepts and doctrines of the Ukrainian society development, which were formed and developed in the 18th - 30s of the 20th century. The Ukrainian people have developed their own understanding of the constitution nature in the course of the long history of the Ukrainian state formation. The historical aspect has also influenced the ideas regarding the restriction of the state power and the social values, which the Constitution ought to reflect. The concepts of national sovereignty, election of the organs of government and selfgovernment of the territorial communities were refined by the Ukrainian history and became its inalienable tradition. The concept of equality of human rights was formed and developed under the influence of the American and European liberalism, Polish patriotism and Russian chauvinism. The concept of the political independence of Ukraine, built on the historical experience, has undergone long evolution from the idea of confederation of the Slavic peoples, a federation and autonomy as a part of other states to the independent state. At the same time, the clerical ideas significantly influenced the development of the ideas about state power, human rights and freedoms. Nationalism as a state-building doctrine developed and became popular in the interwar period as a contrast to socialism and liberalism.
Genesis and Development of the Ukrainian Constitutionalism’ Concepts (XVIII - 30s of the XX century)
Keywords: автономія; незалежність; конституціоналізм; конституція; права і свободи людини; територіальна громада; правова держава; лібералізм; слов'янофільство; націоналізм; демократія; autonomy; іndependence; constitutionalism; constitution; human rights and freedoms; territorial community; rule of law; liberalism; slavophilism; nationalism; democracy